Using online presence data for recommending human resources in the OP4L project - Grandbastien, Monique; Loshkovska, Suzana; Nowakowski, Samuel; Jovanovic, Jelena (My University, 2012)
In order to help and support learning practices, the development of web-based Personal Learning Environments (PLE) is widely adopted. A PLE is a set of services customized by the student. Among these services, resource (either digital or human) recommendation is a crucial one. The paper briefly reviews existing approaches for recommending resources in PLE. Then it describes a novel approach implemented in the OP4L prototype. OP4L is combining Social Web presence data and semantic web technologies, based on an intensive use of ontological models to represent the learning context. Then the paper reports about qualitative studies that were conducted with students on the currently available version of the OP4L prototype. The aim of the study was to get students’ feedbacks about new online presence services offered in a LMS.
Keywords: Web-based learning, social presence, online presence, social semantic web, ontology based resource recommendation